Incidence of and risk factors for Hospital Acquired Infection in a Tertiary Care Hospital of Dhaka, Bangladesh (Bangladesh Journal of Medical Science, 2017)
Objective: Hospital acquired infection (HAI) is a major concern in hospital settings.Methods: This study was conducted to evaluate the incidence of Hospital Acquired Infection (HAI), patient and hospital related factor, offending microorganism and their antimicrobial sensitivity. Data were collected prospectively with patients admitted during study period.Results and discussion: 9.4% respondents were found to develop HAI. 60% patients with more than 3 visitor, 11.9% patient with prior antibiotic therapy and 24% patient with underlying illness developed HAI. 14.6% routine operation case and 24.5% emergency operation case developed HAI. 17.1% patients with invasive device therapy whereas 3.8% patients without any device therapy developed HAI. 31.8% patients having immunosuppressive therapy and 37% patients with frequent transfer within hospital whereas only 6.9% patients without transfer developed HAI. Bacteria isolated from HAI cases were identified to be member of nine different genera. Klebsiella pneumoniae isolated from 33% HAI case, while Acinetobacter baumanii and Escherichia coli isolated from 13% case and Pseudomonas aeruginosa from 14% cases. Only colistin has sensitivity range from 76 to 100% while almost all other isolates were observed multi drug resistance (MDR).Conclusion: Comprehensive strategy should be undertaken to reduce risk of HAI.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.358-369